Sustainability science for water: Bibliometric analysis and social-ecological resilience thinking - Xu, Li (Curtin University, 2015)
Incorporating resilience thinking, the thesis uses bibliometric analysis to identify emerging approaches and technology in sustainability science for water resources. It conducts a resilience-based assessment of a Chinese freshwater lake exposed to the disturbances and impacts of the Three Gorges Dam. A new resilience assessment framework is developed and applied in the case of Dongting Lake. Social networks for community resilience to the environmental changes triggered by the dam are also explored.